Quality improvement at Eastern People Military Hospital - Dung, Hoang Manh; Viet, Truong Hoang; Vu, Tran Thuy (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Quality improvement is a permanent goal of all types of organizations. The change in hospital quality management towards patient satisfaction is an inevitable and objective trend. Objective: Compare the importance level with the implementation level of each criterion according to the IPA matrix to arrange the order of improvement at Eastern People Military Hospital based on the Vietnam Hospital Quality Criteria Set (Version 2.0). Methods: The research design is quantitative with a general analysis method to achieve the goals. Results: Determine the position of each criterion on the IPA matrix and identify improvement directions for the criteria applied at the Eastern People Military Hospital. Conclusion: The article emphasizes the importance of the IPA matrix when evaluating quality at hospitals and suggests directions for improving service quality according to world practices.